Calmodulin/CAMKII inhibition reduces electrical activation heterogeneities caused by mechanical stretch in the myocardium. (25th November 2020) - Martinez-Navarro, H; Del-Canto, I; Cardells, M.J; Genoves, P; Such-Miquel, L; Parra, G; Arias-Mutis, O; Munoz, M; Zarzoso, M; Alberola, A; Chorro-Gasco, F.J; Such, L
Abstract: Introduction: Ca2+/calmodulin-dependant protein kinase (CAMKII) activity in cardiomyocytes plays a crucial role in their contractility. Increased CAMKII signalling has been associated with mechanical stretch, often caused in the border zone of myocardial infarction. CAMKII upregulation causes a mishandling of intracellular calcium, a precursor of multiple pro-arrhythmic mechanisms, such as early afterdepolarisations. Purpose: In this study, we aim to quantify the effects of KN-93 -a CAMKII inhibitor- on wave dynamics, in order to investigate its effectiveness as an anti-arrhythmic agent. Methods: An isolated Langendorff model was constructed based on rabbit hearts (n=18) and posteriorly induced to fibrillation. An epicardial multielectrode array (121 electrodes) was used for recording the electrical activity. Mechanical stretch was induced by pushing the anterior myocardial wall from the left-ventricular cavity. Then, a frequency analysis was conducted for the following conditions: before drug infusion, during infusion, during infusion plus stretch, and during infusion post-stretch. Nine hearts represented the untreated group, and the other nine were infused with KN-93 at a concentration of 10 nM (less than 3% of the IC50 value). Results: Prior to stretch induction, KN-93 caused no effects in the spectral concentration (SC) and average dominant frequency (ADF) calculated on the infused rabbit hearts. Nevertheless, intrasubject measurements revealed statistically significant differences (p<0.05) between hearts infused with KN-93 and the untreated ones when stretch was induced. Changes in SC were milder in the treated than the untreated group (−6% vs −33%). Also, the stretch-induced increase in ADF was more limited in the treated group (+17% vs +40%). Hearts infused with KN-93 shown a higher resistance to stretch-induced electrical abnormalities, potentially due to better regulated intracellular calcium dynamics. Conclusion: CAMKII inhibitors show cardioprotective potential, even at very low concentrations. Further research is required to investigate the therapeutic use of these compounds in conditions of intracellular calcium mishandling and its concomitant life-threatening consequences, such as heart failure or Torsade de Pointes. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Universitat de València; Generalitat Valenciana - Prometeo; Carlos III, CIBERCV